The Influence of Self Confidence on Inmates' Social Skills at a Correctional Institution in Malang - Anabillah, Ardha Reza; Hitipeuw, Imanuel (KnE Social Sciences, 2024)
The prisonisation or socialization program for inmates still shows that there are problems related to social interaction that can lead to anti-social behaviors. For this reason, it is important for inmates to have good social skills and it can also be influenced by a person’s beliefs. For this reason, this study aimed to determine the influence of self-confidence on the social skills of inmates in Class 1 Correctional Institution Malang. The design of this study is causal correlation. This study used a purposive sample and obtained 40 inmates who participated in the socialization program, were aged 20 – 45 years, and had served one-third of their sentences. Two questionnaires in the form of a self-confidence scale and a social skills scale were used to collect data. Data analyses used a simple linear regression technique. The results of the study show that the self-confidence of inmates has a positive and significant effect on the social skills of inmates; with the magnitude of the influence of the self-confidence variable on social skills of 34.7% based on R square. Keywords: prisoner, self-confidence, social skills